The Acceptability of Nonvegetarian Medications in Vegetarian Patients in Otolaryngology. (2nd September 2014) - Haarer, Francesca; Fu, Bertram; Desai, Ketan
Abstract : Objectives: (1) Find out the proportion of vegetarian patients in our department and their knowledge, views, and preferences in receiving nonvegetarian medications. (2) Describe commonly prescribed ear, nose, and throat (ENT) medications in our department and whether they are suitable for vegetarians. Methods: A questionnaire survey was performed in the ENT department of a large southeast England university teaching hospital in the United Kingdom between January and February 2013. A list of commonly prescribed ENT medications in our department was drafted, and their constituents were confirmed with corresponding manufacturers. Results: Forty patients responded to the questionnaire in this period. Responses for the following questions were collected and results were analyzed: (1) Are you vegetarian? Religious/lifestyle choice/others; (2) Do you ask your doctor if he/she is prescribing medication containing animal products?; (3) If you are a vegetarian, would you take any prescribed medication containing animal products?; (4) Do you think a patient should be offered a vegetarian alternative if they prefer/choose? Conclusions: We have found a significant proportion of our patients are vegetarian and that they prefer to have a choice of medications that are suitable for vegetarians if available. We have tabulated a list of commonly prescribed medicines in our department and contacted the relevant pharmaceutical companies, inquiring if their medicines contain any excipients from an animal source. Although the majority of medicines contained no animal‐sourced active components or excipients, a significant proportion did. One of the most common excipients used was gelatine (E441).